Maslahah Mursalah: Analysis of the Legitimacy of a Woman Traveling Without a Mahram in the Contemporary Era - Adibah, Siti Amiratul; Hamidah, Tutik (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
The modern demand for women to migrate for various reasons without a mahram, combined with the need for research on this issue, makes it necessary to examine. Consider that there is a hadith explaining the rule that women must travel with their mahram. This study will analyze maṣlaḥah mursalah regarding women's ability to migrate without a mahram, using literature review methods and the basic theory of maṣlaḥah mursalah researched from several books and journals. The research concluded that, in the context of maṣlaḥah mursalah, permitting women to migrate without a mahram is more beneficial because of certain positive impacts and potential negative impacts, along with other security measures besides the mahram that can ensure women's safety.